PENDAMPINGAN PERBAIKAN INTERIOR MASJID AN NIHAYAH SAMARINDA SEBAGAI UPAYA PENINGKATAN ESTETIKA RUANG IBADAH - Rahman, Rizky Nur; Willis, Tito Bisma May (Jurnal Abdi Insani, 2025)
Masjid An Nihayah, located on Jalan Adam Malik, Karang Asam Ilir Village, Sungai Kunjang Subdistrict, Samarinda City, plays a crucial role as a center for worship and religious activities. However, the interior of the mosque, which has not been updated for a long time, has experienced a decline in aesthetic quality, affecting the comfort of the worshippers. As a place that represents spirituality, an aesthetic update of the interior has become an urgent need. Therefore, this assistance activity aims to enhance the aesthetic quality of the interior of Masjid An Nihayah to create a more comfortable and attractive worship space for the congregation. A participatory approach is used in this activity, involving the analysis of the existing condition, gathering input from the mosque management, and formulating design recommendations. Briefly, the technical planning assistance provided by the service team consists of several stages: the design phase, the preparation of the Budget Plan (RAB), and the construction process assistance phase. This activity resulted in an interior improvement design that highlights aesthetic elements such as the use of harmonious colors, optimal lighting design, and the selection of suitable decorative materials. In addition, this activity strengthens the relationship between academics and the community in supporting development based on local needs. This assistance successfully provided a design solution that improved the aesthetic quality of the mosque's interior and created a more comfortable worship space for the congregation.